Connecting the dots: from nanodomains to physiological functions of REMORINs. Issue 3 (18th December 2020) - Gouguet, Paul; Gronnier, Julien; Legrand, Anthony; Perraki, Artemis; Jolivet, Marie-Dominique; Deroubaix, Anne-Flore; German-Retana, Sylvie; Boudsocq, Marie; Habenstein, Birgit; Mongrand, Sébastien; Germain, Véronique
Abstract : The available information on the plant-specific plasma membrane-bound family of REMORIN proteins points to their potential role as scaffolding proteins in a plethora of cellular processes. Abstract: REMORINs (REMs) are a plant-specific protein family, proposed regulators of membrane-associated molecular assemblies and well-established markers of plasma membrane nanodomains. REMs play a diverse set of functions in plant interactions with pathogens and symbionts, responses to abiotic stresses, hormone signaling and cell-to-cell communication. In this review, we highlight the established and more putative roles of REMs throughout the literature. We discuss the physiological functions of REMs, the mechanisms underlying their nanodomain-organization and their putative role as regulators of nanodomain-associated molecular assemblies. Furthermore, we discuss how REM phosphorylation may regulate their functional versatility. Overall, through data-mining and comparative analysis of the literature, we suggest how to further study the molecular mechanisms underpinning the functions of REMs.